Nature Materials - Dusastre, Vincent; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Research.)
Nature Materials is a multidisciplinary journal aimed at bringing together cutting-edge research across the entire spectrum of materials science and technology. Nature Materials covers all applied and fundamental aspects of the synthesis/processing, structure/composition, properties and performance of materials. Nature Materials provides a forum for the development of a common identity among materials scientists while encouraging researchers to cross established subdisciplinary lines. To achieve this, Nature Materials takes an interdisciplinary, integrated and balanced approach to all areas of materials research while fostering the exchange of ideas between scientists involved in different communities.
Keywords: Condensed matter; Materials science; Optical materials; Electronic materials; Biomaterials; Nanotechnology; Materials Science, general; Optical and Electronic Materials; Biomaterials; Nanotechnology; Condensed Matter Physics